2013
DOI: 10.1016/j.jacc.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Remote Ischemic Post-Conditioning by Intermittent Balloon Inflations in Patients Undergoing Percutaneous Coronary Intervention

Abstract: RIPC by serial balloon inflations and deflations during PCI was found to confer protection against AKI in patients with a non-ST-segment elevation myocardial infarction undergoing PCI. The reduction in the rate of AKI translated into a clear trend (of borderline significance) toward better 30-day clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 22 publications
1
74
0
1
Order By: Relevance
“…RIPost has recently been reported to reduce PCI-related AKI in a randomized study of 225 patients. 43 In that study, the mode of RIPost was cyclic inflations of the stent balloon, after stent deployment, to nominal pressures for 30 seconds. The investigators demonstrated a significant reduction in PCI-related AKI, using the same definition as used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…RIPost has recently been reported to reduce PCI-related AKI in a randomized study of 225 patients. 43 In that study, the mode of RIPost was cyclic inflations of the stent balloon, after stent deployment, to nominal pressures for 30 seconds. The investigators demonstrated a significant reduction in PCI-related AKI, using the same definition as used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, we still perceived a durable clinical benefit of RIPC-treated patients undergoing elective PCI. We think this was attributable to RIPC limiting PCI-induced myonecrosis, but acknowledge that protection of other organs and specifically renoprotection 24 may have also contributed. However, our findings need to be confirmed in a large, multicenter, randomized, control trial adequately powered for clinical events.…”
Section: Study Limitationsmentioning
confidence: 98%
“…Deftereos et al recently provided additional evidence that remote ischemic postconditioning may also be effective in preventing acute kidney damage in intermediate-risk patients (mean Mehran risk score 10). 72 The authors evaluated the renoprotective effect of remote ischemic postconditioning in patients with a non-ST-segment elevation myocardial infarction undergoing percutaneous coronary intervention (N5225). In the intervention group, four 1-minute cycles were performed, each consisting of 30-second inflation of the stent balloon and 30-second deflation.…”
mentioning
confidence: 99%